Psychosocial risks related to the nurse in the psychiatric hospital and management strategies - Maria Carolina Santos Scozzafave; Laura Andrian Leal; Mirelle Inácio Soares; Silvia Helena Henriques
ABSTRACT Objective: To characterize the presence of psychosocial risks related to the work of the nurse in a psychiatric hospital and the strategies for managing these risks. Methods: Qualitative, in which 25 nurses from a psychiatric hospital participated using semi-structured interviews from November 2014 to January 2015. Data analysis was performed using the thematic method. Results: The results showed psychosocial risks related to the work of psychiatric nurses, such as: insufficient academic training; lack of preparation and maintenance of equipment; poor relationship with colleagues; shortage of human resources and lack of capacity building; conflict between the demands of the home and work, as well as strategies for managing psychosocial risks such as family, cinema, music, reading, among others. Final considerations: This study should provoke the reflection of managers and future nurses regarding the working conditions in a psychiatric hospital and possible psychosocial risks to which they are exposed.